Abate application practices in the Guinea worm endemic region of Gambella, Ethiopia: identification of elimination gaps - Yamlak Gindola; Desalegn Getahun; Khogali Ahmed Mohammed; Edward Mberu Kamau; Bienvenu Salim Camara; Mesfin Wossen; Kassahun Demissie; Sintayehu Abdela; Gashaw Gebrewold; Girmay Hailu; Mesfin Tegistu; Akwoma Okugn; et al. (Journal of Infection in Developing Countries)
Introduction: Guinea worm disease is caused by Dracunculus medinensis. Transmission of the disease depends on vectors (copepods). Abate applications in targeted water sources to control copepod is the main intervention. The aim of this study was to assess vector control practice in the guinea worm endemic region of Gambela, Ethiopia and to identify elimination gaps.